Cytogenomic results following high-chance non-invasive prenatal testing: a UK national audit. (2020) - Togneri, Fiona S.; Allen, Stephanie K.; Mann, Kathy; Holgado, Elaine; Morgan, Sian
Abstract: Objective: Non-invasive prenatal testing (NIPT) is increasingly being adopted as a screening test in the UK and is currently accessed through certain National Health Service healthcare systems or by private provision. This audit aims to describe reasons for and results of cytogenomic investigations carried out within UK genetic laboratories following an NIPT result indicating increased chance of cytogenomic abnormality ('high-chance NIPT result'). Method: A questionnaire was sent out to 24 genetics laboratories in the UK and completed by 18/24 (75%). Results: Data were returned representing 1831 singleton pregnancies. A total of 1329 (73%) invasive samples were taken following NIPT results showing a high chance of trisomy 21; this was confirmed in 1305 (98%) of these by invasive sampling. Trisomy 21 was confirmed in >99% of patients who also had high-screen risk results or abnormal scan findings. Amongst invasive samples taken due to NIPT results indicating a high chance of trisomy 18, 84% yielded a compatible result, and this number dropped to 49% for trisomy 13 and 51% for sex chromosomes. Conclusion: In the UK, the majority of patients having invasive sampling for high-chance NIPT results are doing so following an NIPT result indicating an increased chance of common trisomies (92%). In this population, NIPT performs particularly well for trisomy 21, but less well for other indications.